Analysis on Methylene Oxidation in Aromatic Molecules: Achieving Chemoselective Methylene Oxidation in the Presence of Fragrant Functionalities (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Regardless of critical advancement in the improvement of site-specific aliphatic C–H oxidations over the previous decade, the capacity to oxidize solid methylene C–H bonds within the sight of all the more oxidatively labile fragrant functionalities remains a noteworthy unsolved issue. Such chemoselective reactivity is exceptionally attractive for empowering late-arrange oxidative derivatizations of pharmaceuticals and therapeutically significant regular items that frequently contain such usefulness. Here, we report a basic manganese little atom impetus Mn(CF3–PDP) framework that accomplishes such chemoselectivity through an unforeseen cooperative energy of impetus plan and corrosive added substance.